Epistemological Beliefs and Information-Seeking Behavior of Graduate Students in Lanao Del Sur, Philippines - Macalantong-Casan, Faishanie (Journal of Interdisciplinary Perspectives, 2024)
This study examined the epistemological beliefs and information-seeking behavior of 350 first-year Lanao del Sur graduate students. Descriptive statistics were used for frequency, percentage, mean, and standard deviation. Moreover, inferential statistics such as Chi-Square, Analysis of Variance (ANOVA), and regression analysis were used to test the significant difference and relationship between the independent and dependent variables. The salient findings include epistemological beliefs regarding the acquisition of knowledge, which got the highest mean, while the learning speed got the lowest mean. The level of information-seeking behavior was highest in preparing to present. The findings disclosed a significant difference in the information-seeking behavior of the graduate students when grouped according to their characteristics. Epistemological beliefs showed a positive relationship towards information-seeking behavior. This means that the null hypothesis is rejected. In conclusion, most respondents have the highest degree of epistemological beliefs towards acquiring knowledge and have the highest level of information- seeking behavior in preparing to present. Their’ information-seeking behavior varies according to their characteristics, which include sex, age, civil status, course enrolled in, number of hours spent in Internet search, and nature of work. The epistemological beliefs have a bearing on information-seeking behavior. It is then recommended that the graduate students be assisted in developing thorough and productive research skills. Second, schools should encourage librarian and faculty collaboration in teaching research methods to graduate students.